Mental Health and Psychosocial Support During COVID-19: A Review of Health Guidelines in Sub-Saharan Africa - Molebatsi, Keneilwe; Musindo, Otsetswe; Ntlantsana, Vuyokazi; Wambua, Grace Nduku (Frontiers in Psychiatry, 2021)
The COVID-19 pandemic brought in its wake an unforeseen mental health crisis. The World Health Organisation published a guideline as a way of supporting mental health and psychosocial well-being of different groups during this pandemic. The impact of the pandemic has pushed governments to put measures in place to curb not only the physical health of individuals but their mental health and psychosocial well-being as well. The aim of our paper was to review mental health guidelines of some Sub Saharan African (SSA) countries: i) to assess their appropriateness for the immediate mental health needs at this time, ii) to form as a basis for ongoing reflection as the current pandemic evolves. Guidelines were retrieved openly from internet search and some were requested from mental health practitioners in various SSA countries. The authors designed a semi-structured questionnaire, as a self-interview guide to gain insight on the experience of COVID-19 from experts in the mental health sector in the various countries. While we used a document analysis approach to analyse the data, we made use of the Mental Health Preparedness and Action Framework to discuss our findings. We received health or mental health guidelines from 10 SSA countries. Cameroon, Kenya, South Africa, Tanzania, and Uganda all had mental health guidelines or mental health component in their health guidelines. Our experts highlight that the mental health needs of the people are of concern during this pandemic but have not been given priority. They go further to suggest that the mental health needs are slightly different during this time and requiring a different approach especially considering the measures taken to curb the spread of disease. We conclude that despite the provision of Mental Health and Psychosocial Support guidelines, gaps still exist in making them inadequate to meet the mental health needs of their communities.